URBAN ECOSYSTEM SERVICES FOR CLIMATE CHANGE ADAPTATION IN DWARKA, DELHI: INSIGHTS FROM GLOBAL CASE STUDIES - Naaz, Shaila; Mehrotra, Nirmita (International Journal of Research -GRANTHAALAYAH, 2026)
Rapid urbanisation and climate change are intensifying environmental risks in metropolitan regions, particularly in cities of the Global South. Indian cities such as Delhi are increasingly exposed to extreme heat, urban flooding, air pollution, and declining environmental quality, highlighting the urgent need for effective climate change adaptation strategies. Urban ecosystem services (UES), including regulating, provisioning, cultural, and supporting services, are increasingly recognised as a critical framework for ecosystem-based adaptation (Elmqvist et al., 2015; Kabisch et al., 2017). This study examines the role of urban ecosystem services in climate change adaptation within Dwarka Sub-City, Delhi, informed by insights from global case studies across Europe, North America, and Asia. International case studies demonstrate that regulating services such as microclimate cooling, air-quality regulation, and stormwater retention provide the strongest adaptation benefits, particularly in high-density urban environments (Larondelle & Lauf, 2016; Plieninger et al., 2022; Wang et al., 2016). Comparative analysis with global case studies underscores the importance of integrating UES into urban planning frameworks through sector-wise ecosystem service budgeting, urban tree-canopy targets, rooftop greening incentives, and coordinated blue-green infrastructure development (Zari et al., 2020; Brandt et al., 2016). The study contributes to urban climate governance literature by demonstrating how UES can function as an operational planning framework for climate adaptation in Indian metropolitan contexts. By contextualising global best practices within local socio-ecological and institutional conditions, the research offers transferable insights for rapidly urbanising cities facing similar climate challenges. Embedding UES-based strategies into statutory planning and participatory governance mechanisms is essential for strengthening long-term urban resilience in climate-stressed Indian cities.